المتغيرات التقنية و انعكاساتها في النظام التصميمي للمنتج الصناعي - مهدي، وليد محمد (الجامعة المستنصرية - كلية التربية الأساسية, 2015)
تناولت الدراسة الموسومة المتغيرات التقنية وانعكاساتها في النظام التصميمي للمنتج الصناعي) الكثير من المفاهيم والأفكار التي قسمت المجال لتعدد المتغيرات التقنية واتجاهاتها التصميمية في منتجات السيارات الكورية الجنوبية التابعة لشركة (كيا). ويهدف البحث إلى بيان المتغيرات التقنية وفاعليتها في الجوانب الشكلية والأدائية للمنتج الصناعي في ظل مراحل المتغيرات التقنية الجديدة والمتسارعة. وتتأتى أهمية هذه الدراسة في الحقل الصناعي لما لها من أهمية في عملية بناء أسس وقواعد معرفية وعلميه لمعاني الأشكال ووظائفها الجديدة والمعاصرة. وقد اشتملت حدود الدراسة الإضاءة الأمامية لسيارات (كيا) المتوافرة في الأسواق المحلية لمدينة بغداد خلال المدة الزمنية 2013 حصرا. وقد تكونت الدراسة من خمسة فصول تضمن الفصل الأول على مشكلة البحث وأهميته وأهدافه وحدوده وتحديد المصطلحات، أما الفصل الثاني فقد تضمن الاطار النظري على مبحثين احتوى المبحث الأول والمتغيرات التقنية في منجزات التصاميم الصناعية) وتضمن المبحث الثاني (الأنظمة التصميمة للمنتج الصناعي والمتغيرات التقنية)، وتناول الفصل الثالث إجراءات البحث، إذ تم استخدام طريقة المنهج الوصفي (دراسة الحالة) في عملية وصف وتحليل نماذج العينة والتي مثلت 25% من مجتمع البحث. ولقد اعتمد الباحث على المؤشرات التي افرزها الاطار النظري والمستند على المصادر والمراجع الأجنبية وشبكة المعلومات (الإنترنت) وعلى الملاحظة. في حين تضمن الفصل الرابع على وصف وتحليل نماذج العينة والمتكونة من (2) أنموذج تم اختيارها بشكل قصدي بعد بناء استمارة تحددت بموجبها محاور التحليل الأساسية، وتوصل الباحث إلى أهم النتائج: 1 -اتخذت الدينامية الخطية حالة بإضفاء صيغ الملائمة الشكلية والموضوعية لتصميم المنظومة الضوئية الأمامية فقد أعطي الخط مسارات اتجاهية حركية قابلة للنمو والتطوير. 2-التوليفيات التصميمية للنماذج نفذت بأساليب متعددة في تقنيات الإظهار الشكلي وبسياقات جديدة بعيدا عن النمطية التقليدية. 3- تجسيد مبدأ التوازن المنتظم من خلال التكرار والتشابه في الأجزاء التكوينية ونسبها في القيم اللونية والملمسية والشكلية والحجية. 4 شكلت مادتي الزجاج واللدائن البنية التكوينية لمنظومة الإضاءة الأمامية محققة أداءا وظيفيا وقيما في الجمالي الشكلية والتعبيرية. أما الاستنتاجات التي خرجت بها الدراسة فهي: 1- إن فاعلية العلاقات البنائية أظهرت قدرة واسعة لتشكيل تكوينات تصميمية تعمل بدورها على تأسيس سياقات تصميمية من شانها استحداث تصاميم متطورة. 2- شكلت المتغيرات التقنية والتنوع في العناصر المادية إعطاء الخصوصية التصميمية لمنظومة الإضاءة الأمامية. 2- تشكل عملية اختيار مواد الزجاج واللدائن عناصر رئيسية في إنتاج منظومة الإضاءة الأمامية لما تمتلكه هذه المواد من الكفاءة والمتانة والجودة، فضلا عن قابليتها العالية في القولبة والتشكيل والتغير الشكلي. ووفقا للنتائج والاستنتاجات توصل الباحث إلى مجموعة من التوصيات و المقترحات والاتجاهات التصميمية.
The marked study deals with "the techniques variables and their reflections in design system for industrial product ". many concepts and thoughts divided the scope due to multi techniques cars and their design trends in the products of South Korean vehicles belonging to ( KIA ) company. The research aimed at showing the techniques variables and their efficiency in both formal and performance aspects of the industrial product according to new and rapid techniques variables . The importance of this study comes out from industrial field due to its consideration in the process of establishing of cognitive and scientific bases and rules for the meaning o the forms and their new and modern functions . The scope of the study included the front light of the car ( KIA )which are available in local markets in the city of Baghdad during exclusive period of 2013 . The study consisted of five chapters. Chapter one includes the problem of the research , its importance , its objectives, its limitations and defining the terms . Chapter two includes the theoretical framework which consist of two categories , the first one is dealing with " techniques variables in the achievement of industrial designs " . The second category is dealing with "design systems of industrial product and techniques variables". Chapter three is dealing with the procedures of the research in which the researcher used descriptive method( case study ) in the process of theoretical framework the samples of the specimen which represented 25% from the society of the research . The researcher depended on some indicators separated from theoretical framework according to foreign references and internet and observations . Chapter four included description and analysis the samples of the specimen which consisted of ( 2 samples ) selected intentionally after preparing a form to define the main analysis pivot . The researcher has reached the following results:- 1. Taking the dynamic linear as a state to impart formal harmony pattern and objectivity to design front light system in which the line present kinetics direction paths can be developed and outgrow . 2. Design synthesis of the samples have carried out in multiple methods in formal demonstrating techniques with new rules away from traditional style. 3. Embodying systemized balanced principle through assimilation and repetition in formation parts and its rate in color value , touching ,formal and pretext . 4. Both materials glass and plastics represented the formation structure of front light system achieving valuable performance and function in the formal and expressional field . The conclusions of the study are : 1. The efficiency of structure relationship[p has showed great capacity to form design components leading to establish design regulations participating in innovating developed design . 2. The techniques variables and diversity represented in material elements which gave design privacy for the front light system . 3. Selection process of glass and plastics the main elements in producing front light system due to its efficiency and high quality , besides their high ability in modeling , formation and formal change . According to the results and conclusions , the researcher has reached several recommendations , suggestions and design trends .
Keywords: التقنية -- المنتجات الصناعية -- التصميم